Patient Compliance in the Setting of BI‐RADS Category 3: What Factors Impact Compliance With Short‐Term Follow‐Up Recommendations?. Issue 1 (17th November 2016) - Borders, Marisa H.; Cheng, Lucy; Fitzpatrick, Kimberly A.; Krupinski, Elizabeth A.
Abstract: The study aims to define how imaging findings, patient demographics, patient–provider interactions, and health care practices may affect a woman's decision to follow‐up in the setting of a BI‐RADS Category 3. A total of 398 women from the University of Arizona Breast Imaging Center with a BI‐RADS Category 3 assessment for mammography and/or ultrasound findings were evaluated between February 2012 and June 2014. Demographic information was analyzed for all patients, regardless of follow‐up. Women who returned for follow‐up within the recommended time period were given one survey at the time of their follow‐up appointment, and women who returned for follow‐up, but later than recommended, were given a separate survey to complete. Age, palpability of a lesion, and menopause status were related to follow‐up. Self‐rated general health was the only factor found to be associated with the decision to follow‐up on time. The majority of patients who followed up on time reported that mailed reminder cards were the primary practice that prompted follow‐up. Of patients who followed up later than recommended, the major reason was "no time." The findings suggest that additional counseling regarding the benefits of short‐interval imaging follow‐up might be advantageous for patients.